Low income and education are associated with greater ASCVD risk scores among adults in the US - Julien O. Tremblay; Lauren Nahodyl; Robert A. Mesa; Lilliana Vilchez; Tali Elfassy (Preventive Medicine Reports, 2024)
Introduction: Social determinants of health (SDOH) are fundamental causes of poor cardiovascular health, yet cardiovascular disease (CVD) risk assessment tools exclude SDOH. Our objective was to determine whether SDOH are independently associated with CVD risk in US adults. Methods: Utilizing the National Health and Nutrition Examination Survey (NHANES), we combined years 1999–2018 and included participants aged 40–79 without history of CVD and with information to calculate CVD risk (n = 21,694). Ten-year risk of atherosclerotic CVD (ASCVD) was calculated using the American Heart Association/American College of Cardiology (AHA/ACC) pooled cohort equations. We used linear regression models to estimate the association between SDOH and ASCVD risk, after adjusting for demographic factors. All analyses accounted for the complex survey design. Results: Mean age was 54.7 years, with 52.7 % female, 73.8 % non-Hispanic White, 9.4 % non-Hispanic Black, and 10.7 % Hispanic. From adjusted models, compared with an income of ≥ $75 K, ASCVD risk was greater by 3.06 (95 % CI: 2.65, 3.47) among those with income < $25 K, by 1.55 (95 % CI: 1.21, 1.89) among those with income $25 K–<$55 K, and by 1.20 (95 % CI: 0.84, 1.56) among those with income $55 K–<$75 K. Compared to college graduates, ASCVD risk was greater by 3.09 (95 % CI: 2.56, 3.62) among those with less than a high school education, by 1.65 (95 % CI: 1.31, 200) among those who were high school graduates, and by 1.41 (95 % CI: 1.11, 1.72) among those with some college education. Conclusion: We found strong graded associations between lower income and lower educational attainment with greater CVD risk.